Socioeconomic status and problem behaviors in young Chinese children: A moderated mediation model of parenting styles and only children - Lin, Xunyi; Zhang, Yifan; Liao, Yutong; Xie, Wanlin (Frontiers in Psychology, 2023)
This study tested a moderated mediation model of child number (CN) and parenting styles (PS) in the relationships between family socioeconomic status (SES) and young children’s problem behaviors (PB). A sample of 1101 children (Mage = 4.90 years, SD = 1.07) and their parents participated in this study. Parents reported on PS, SES, and children’s PB. Results showed that: (1) SES was positively related to authoritative parenting and negatively related to authoritarian parenting; (2) Problem behaviors were negatively related to authoritative parenting and positively related to authoritarian parenting; (3) Authoritative parenting and authoritarian parenting mediated the relationship between SES and PB; (4) Singleton moderated the relationship between SES and PB. The combination of only children and low levels of SES could lead to high levels of PB. In contrast, the combination of non-only children and high levels of SES could lead to high levels of PB. At the same SES, only children had higher levels of PB compared to non-only children. This moderated mediation model includes different family environmental factors, which helps clarify the complex mechanism of SES influencing young children’s PB.